Template synthesis of Zn2TiO4 and Zn2Ti3O8 nanorods by hydrothermal-calcination combined processes - Jirapong Arin (2018)
© 2017 Elsevier B.V. ZnO nanorods coated with TiO 2 nanoparticles of 2:1 and 2:3 mole ratios Zn:Ti were synthesized by 120 °C and 12 h hydrothermal reaction. Upon calcination the nanocomposites at 750 °C for 5 h, they were transformed into Zn 2 TiO 4 and Zn 2 Ti 3 O 8 nanorods. The XRD results revealed the presence of zinc orthotitanate (Zn 2 TiO 4 ) and zinc polytitanate (Zn 2 Ti 3 O 8 ) by calcination of the precursors with 2:1 and 2:3 mole ratios Zn:Ti. SEM and TEM analyses show TiO 2 nanoparticles coated on ZnO nanorods. Upon calcination at high temperature, TiO 2 nanoparticles fused and incorporated in ZnO nanorods to form zinc orthotitanate and zinc polytitanate nanorods. Their formation mechanism was proposed and discussed in this research.